∫ log(x) dx

  • Google+ icon
  • LinkedIn icon
  • 1070 views

Using "Integration by parts" or "reverse chain rule" .

Recall formula for intergration by parts: "∫f'(x) g(x) dx = f(x)g(x) - ∫f(x)g'(x)dx"

Then set f'(x) = 1, g(x) = log(x). Can calculate f(x) = x, g'(x) = 1/x.

Then plug into the formula to get ∫log(x)dx = xlog(x) - ∫1 dx = xlog(x) - x +c

Michael T. A Level Maths tutor, GCSE Maths tutor, A Level Computing t...

About the author

is an online A Level Maths tutor with MyTutor studying at Durham University

Still stuck? Get one-to-one help from a personally interviewed subject specialist.

95% of our customers rate us

Browse tutors

We use cookies to improve your site experience. By continuing to use this website, we'll assume that you're OK with this. Dismiss

mtw:mercury1:status:ok